Terapi Murottal Terhadap Nyer Pasien Ulkus Diabetes Melitus : Studi Kasus - Suarda, Andi Ainun Dzatti Iffah; Ashar, Maria Ulfah; Jamaluddin, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2024)
Background: The incidence of type 2 diabetes mellitus is between 85% and 95% of the world's population suffers from diabetes mellitus. Diabetes occurs when the sufferer's body is unable to absorb glucose into cells and use it as energy. This condition ultimately causes excess glucose to build up in the body's bloodstream. Diabetic foot ulcers are the most common complication in people with diabetes mellitus and can lead to amputation. In cases of diabetic foot ulcers, patients always require pain management. One non-pharmacological therapy that can be used to reduce pain is murottal therapy. Objective: The aim of this study was to analyze nursing care for patients with a medical diagnosis of type 2 diabetes mellitus complicated by diabetic ulcers with acute pain problems using murottal therapy. Methods: This research is a case study using data collection techniques of observation, interviews, physical examination and documentation. Murottal therapy is given for 15 minutes once a day for 3 consecutive days. Results: Murottal therapy has been proven to be effective in helping reduce or reduce pain in diabetic ulcer patients. On the primary day, the patient's pain scale was 7 (severe) and by the third day, the patient's pain scale had diminished to 4 (moderate). Conclusion: Murottal therapy intervention provided good changes in reducing the pain scale.